STUDYING THE VARIETY OF VISUAL ARTS GENRES (Neo Scientific Peer Reviewed Journal, 2024)
Fine art encompasses a wide range of creative expressions, each of which is characterized by its own styles, themes, and styles. This scientific article sheds light on the study of various genres of visual art, their specific characteristics and historical significance. By reviewing prominent examples and analyzing their artistic elements, this article aims to provide a comprehensive review of various genres in the field of visual arts. The article discusses traditional genres such as portraiture, landscape, and still life, as well as modern and contemporary genres such as abstract art, pop art, and conceptual art. By exploring the complex interplay between genres, this article provides insight into the evolution of artistic expression and the cultural contexts that shaped their development.